PENGARUH MEDIA BONEKA TANGAN TERHADAP KETERAMPILAN MENYIMAK SISWA PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS II SDN 08 CAKRANEGARA - Intan Cahyani EA; Johan Mahyudi; Fitri Puji Astria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effect of hand puppet media on students' listening skills in Indonesian language subjects for class II students at SDN 08 Cakranegara. This research is research with a quantitative approach that analyzes the influence of variable x (hand puppet media) on variable y (listening skills). The research method used is the Pretest-Posttest Control Group Design method. The subjects in this research were all class II students at SDN 08 Cakranegra where class IIA was a control class with a total of 28 students while class IIB was an experimental class with a number of 27 students. The data collection techniques used in this research were tests and observations, research instruments used. used were multiple choice test question sheets and essays (Pretest and Posttest) and observation sheets to determine the influence of hand puppet media. The data analysis technique begins with a prerequisite test, namely the normality test using the Kolmogrov Smirnov test with a significance level of 5% (0.05) and continues with the homogeneity test using the Levene test. Next, test the hypothesis using the independent sample t test. Based on calculations for hypothesis testing at a significance level of 5%, t-count = 10.77, while t table = 1.67356. So t count > t table and the 2-tailed sig value is 0.00 < 0.05, so the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This means that the use of hand puppet media has an influence on the listening skills of class II students at SDN 08 Cakranegara.